Hubungan Usia, Jenis Kelamin, Tingkat Pendidikan, dan Durasi Penyakit dengan Mekanisme Koping pada Pasien Diabetes Melitus Tipe 2 - Ernawati Ernawati (Universitas Faletehan, 2026)
Studies showed that diabetes-related distress and coping are influenced by sociodemographic and illness-related factors. This study examined the associations of age, gender, educational level, and duration of illness with coping mechanisms among patients with T2DM. This quantitative analytic study used a cross-sectional design and was conducted at Singandaru Public Health Center, Serang City from April to May 2023. A total of 30 respondents were recruited using total sampling. Data were collected using a 20-item coping-mechanism questionnaire scored on a Likert scale. Univariate analysis was used to describe respondent characteristics, bivariate analysis to assess associations between independent variables and coping mechanisms, and multivariate analysis to identify the most dominant factor. Most respondents were 46-55 years old (63.3%), female (53.3%), had junior high school education (43.3%), had been living with diabetes for 2 years (43.3%), and demonstrated adaptive coping mechanisms (80.0%). Bivariate analysis showed significant associations between coping mechanisms and age (p < .001), gender (p = .044), educational level (p = .001), and duration of illness (p = .032). In the multivariate model, age remained the most dominant factor (B = -0.693, p = .023). Age, gender, educational level, and duration of illness were significantly associated with coping mechanisms among patients with T2DM, with age emerging as the strongest predictor. These findings highlight the need for primary-care interventions that integrate psychosocial assessment, tailored education, and emotional support.